Corporate environmental disclosure, earnings management and the moderating effect of state ownership in Chinese manufacturing firms - Yong, Mengsu (2022)
This paper examines the impact of environmental disclosure on earnings management in Chinese listed manufacturing firms over the period 2018-2020 and the moderating effect of state ownership on this relationship.